A patient‐specific algorithm to achieve commissural alignment with Acurate Neo: The sextant technique. Issue 6 (7th May 2021) - De Marco, Federico; Casenghi, Matteo; Spagnolo, Pietro; Popolo Rubbio, Antonio; Brambilla, Nedy; Testa, Luca; Bedogni, Francesco
Abstract: Aims: The aim of this proof‐of‐concept study was to investigate safety and efficacy of a CT‐scan based patient‐specific algorithm to maximize coronary clearance and secondarily to achieve anatomically correct commissural alignment with the Acurate Neo device. Method and results: A total of 45 consecutive patients undergoing TAVR with the Acurate Neo THV were prospectively enrolled in the study. Mean age was 81.6 ± 5.5 years, mean STS score was 6.1 ± 3.7. Device success rate was 100%. Aim of the technique was to rotationally deploy the TAVR device with a commissure lying on the bisector between the coronary ostia as calculated on the pre‐procedural CT‐scan. At post‐TAVR CT‐scan, coronary clearance was achieved in 98% of patients with no cases of severe coronary artery overlap. In 42 out of 45 patients, THV was aligned or, at most, mildly misaligned; there were 2 cases of moderate misalignment without any case of severe misalignment. Post‐TAVR selective coronary artery engagement was attempted and succeeded in all patients (100%). Conclusion: Our CT‐scan based patient‐specific algorithm is safe and proven to be effective in avoiding coronary artery overlap and providing commissural alignment with Acurate Neo in all treated patients.